Does Tuition Fee Impact Student Effort in Higher Education? The Effect of Scholarship Provision - Arfan, Tobi; Renaldo, Zainal Arifin (Politeknik Caltex Riau, 2024)
This research examines whether there is an influence of the tuition fees paid by students on students' efforts in academics. This research uses data from Caltex Riau Polytechnic (PCR) students for the period 2017 to 2022. The data is secondary data from the PCR academic system obtained from the PCR Academic, Student Affairs, and Finance sectors. Testing was carried out using the difference in difference (DID) method approach with the help of the Stata 17 application. The results of this study showed that there was a significant difference in students' grades after receiving a scholarship as a reduction in tuition fees. Students who receive scholarships tend to increase their efforts in maintaining grades and improving their college grades. This can be used as input for stakeholders, both campuses and scholarship providers, especially who is entitled to be given a scholarship and when the scholarship should be given.